Case Series: Corneal Epithelial Macrocysts in Scleral Contact Lenses Post–penetrating Keratoplasty. Issue 7 (July 2018) - Nguyen, Linda Trang; Yang, David; Vien, Lee
Abstract : SIGNIFICANCE: Transitory corneal epithelial macrocysts associated with scleral contact lens wear post–penetrating keratoplasty are observed in areas of corneal edema. The macrocysts do not appear to result in complications that would prevent successful wear of scleral contact lenses. PURPOSE: The purpose of this study is to report three cases of transitory corneal epithelial macrocysts associated with scleral lenses in post–penetrating keratoplasty corneas. CASE REPORTS: Three cases including anterior segment photographs and anterior segment optical coherence tomography highlight the clinical presentation of transient corneal epithelial macrocysts. CONCLUSIONS: Corneal edema and anatomical alterations after penetrating keratoplasty along with the negative pressure underneath a scleral contact lens are hypothesized to have caused the transient epithelial macrocysts observed in these cases. Because of the transitory nature of these cysts without evidence of consequent corneal damage or cyst rupture over years of observance, we believe that it is safe for these patients to continue wearing scleral contact lenses with routine follow-up.